2015
DOI: 10.1186/s13018-015-0314-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Evaluation of low-cost custom made VAC therapy compared with conventional wound dressings in the treatment of non-healing lower limb ulcers in lower socio-economic group patients of Kashmir valley

Abstract: BackgroundNegative-pressure wound therapy is a technique to achieve wound healing in patients with non-healing wounds of the lower limb; vacuum-assisted closure (VAC) therapy is a technique to accelerate the healing of non-healing ulcers that fail to heal on their own (primary healing) (Plast Reconstr Surg 117:193–209S, 2006).Delayed wound healing or non-healing of ulcers is a significant health problem, particularly in older adults.The efficacy of VAC dressings has been demonstrated in several randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
0
14
0
3
Order By: Relevance
“…It has been reported that a low-cost negative pressure wound therapy can be beneficial to the patients with chronic wounds of the lower extremity in lower socioeconomic groups. 4 In comparison to our study, it was based on an Indian population and the negative pressure was achieved by connecting the suction tube to a vacuum in the wall, not to the suction machine. Despite its adequacy, it has to be stated that the study had to be withdrawn because of the lack of ethics committee approval.…”
Section: Discussionmentioning
confidence: 86%
“…It has been reported that a low-cost negative pressure wound therapy can be beneficial to the patients with chronic wounds of the lower extremity in lower socioeconomic groups. 4 In comparison to our study, it was based on an Indian population and the negative pressure was achieved by connecting the suction tube to a vacuum in the wall, not to the suction machine. Despite its adequacy, it has to be stated that the study had to be withdrawn because of the lack of ethics committee approval.…”
Section: Discussionmentioning
confidence: 86%
“…Seventeen studies were excluded for the following reasons: did not meet inclusion criteria (n = 5); not an RCT (n = 4); did not describe PIs (n = 4); did not compare with SWC (n = 2); review or case (n = 2). Sixteen studies 26‐41 , which were published from 2002 to 2017 matched the eligibility criteria and were included in the final qualitative study. All the studies consistently reported positive effects of NPWT application.…”
Section: Resultsmentioning
confidence: 99%
“…17 Es aconsejable apoyarse del sistema de presión negativa, en la medida que se cuente con ella, ya que (como sucedió en este caso) proporciona fijación del injerto, evita fuerzas de cizallamiento, lo mantiene húmedo y libre de acúmulo de líquidos que pudieran favorecer el desarrollo de biofilm, proliferación de microorganismos y como consecuencia la falta de integración o pérdida de éste, proporcionando excelentes resultados. 18 En 1969, Belloste propuso el realizar perforaciones a la tabla externa del cráneo para promover tejido de granulación como parte del tratamiento de lesiones en la piel cabelluda. En 1871, Netolitzky popularizó la colocación de injertos dérmicos sobre el tejido de granulación para promover una mejor cicatrización.…”
Section: Discussionunclassified
“…El uso de los injertos de espesor parcial demuestran su beneficio en la cobertura primaria, en comparación de otras técnicas; asimismo, el uso de expansores tisulares sigue siendo una herramienta vital para disminuir las secuelas estéticas. 15,[16][17][18][19][20] El manejo en este paciente demuestra que las técnicas son reproducibles y se pueden asociar los recursos actuales como el sistema de presión negativa para la reparación de heridas complejas en la piel cabelluda (SCALP). En adición, esta técnica quirúrgica es más fácil y rápida de realizar y con menos comorbilidades que otras técnicas descritas.…”
Section: Discussionunclassified